Increasing Student Learning Achievement Through Madrasah Head Strategy Management - Idrus, Ali; Mohzana, Mohzana; Jarmita, Nida; Rahman, Khalid; Shobri, Muwafiqus (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study aims at the Principal's Strategy for Improving Student Achievement at MAN 1 Mojokerto. 2. What are the supporting and inhibiting factors in implementing the Principal's management strategy in improving student achievement at MAN 1 Mojokerto? The method used in this research is qualitative with a case study type in conducting research. In making observations, the researcher acts as participatory and non-participatory observers, namely by participating in teaching and learning activities as well as other activities such as seminars and study groups, then as later as non-participatory observers the researcher observes activities that do not allow researchers to participate in such as activities evaluation and others. The results of the study show that in order to support the principal's strategy through the quality of human resources, infrastructure, learning materials, and rewards.